Muriqui House: conservation management to support the recovery of the northern muriqui Brachyteles hypoxanthus in Ibitipoca, Minas Gerais, Brazil - Fabiano R. de Melo; Fernanda P. Tabacow; Priscila Maria Pereira; Marcello S. Nery; Leandro S. Moreira; Érika Procópio Tostes Teixeira; Danilo Simonini-Teixeira; Mônica Valença-Montenegro; Karen B. Strier; Leandro Jerusalinsky (Oryx)
Ensuring the demographic and genetic viability of small populations of threatened primates requires a range of management approaches. Here we describe a novel mixed in situ and ex situ management project that was developed to restore a population of the Critically Endangered northern muriqui Brachyteles hypoxanthus. This isolated population, located in Ibitipoca, Lima Duarte, Minas Gerais, Brazil, had declined to two adult males and would have gone extinct without intervention. A first attempt at in situ management in 2017 involved the translocation of a solitary female from another region, but this female did not associate or interact with the males and disappeared after 9 months. We thus initiated a second and ongoing ex situ management project that involved constructing a complex consisting of a large, open-air enclosure abutting a small patch of forest surrounded by an open area in the process of restoration, all of which is protected by electric fencing. The entire area within the fencing is called Muriqui House. The two Ibitipoca males and two solitary, wild females from another location were captured and released into the enclosed part of Muriqui House between March 2019 and January 2020 and into the forested part of Muriqui House in February 2020. The birth of an infant in this group in November 2020 and the acceptance by the group of a third female translocated from another area in January 2021 demonstrate the potential of this approach for the recovery of this isolated population, with positive implications for the conservation of the species.